Cultural History Teaching and Patrimony in the Popular Culture Museum of the National University of Costa Rica (UNA) - Cubero Barrantes, Guillermo (2019)
The Popular Culture Museum history is begins with its opening to the public in 1994. Its contact with its audiences takes place through various pedagogical strategies, such as ceramic murals, related to daily life in the Costa Rican Central Valley, an exhibition about the coffee farms history and puppet workshops.